PERANCANGAN APLIKASI E-KANTIN BERBASIS WEBSITE MENGGUNAKAN FRAMEWORK LARAVEL: STUDI KASUS: KANTIN FTI UKSW - Juan Raynaldi; Ramos Somya (Jurnal Pendidikan Teknologi Informasi (JUKANTI), 2023)
Canteens are one of the important facilities in various institutions, such as schools, campuses and offices, which provide food and drinks for visitors. However, many canteens still use conventional systems, causing long queues, user discomfort and difficulty getting information on menu availability. This research discusses the design of a website-based E-canteen application using the Laravel framework with a case study at the Satya Wacana Christian University (UKSW) FTI Canteen. Several stages of application design carried out are collecting research data through questionnaires, analyzing system requirements, developing applications using the Waterfall method and system design using UML diagrams, implementing web-based applications using the Laravel framework and MySQL database, testing application prototypes using black box testing, and evaluating system. which will be used by users through a questionnaire, from the results of the questionnaire it was obtained that the application feasibility was 89%, which means that the website-based e-canteen application prototype is feasible and can be useful for sellers and buyers.